2012
DOI: 10.1177/1356336x12450792
|View full text |Cite
|
Sign up to set email alerts
|

Self-identity as a component of the Theory of Planned Behaviour in predicting physical activity

Abstract: This study aimed to investigate the role of self-identity, defined as salient and enduring aspects of one’s self-perception (Sparks, 2000), in relation to adolescent physical activity (PA) intentions within the Theory of Planned Behaviour (TPB). School students aged 12 to 18 from two cultural groups (Estonia and Spain) completed measures of attitudes, subjective norms, perceived behavioural control, self-identity, and intentions for PA. Four weeks later participants completed self-reported measures of PA. A st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
32
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 44 publications
10
32
1
Order By: Relevance
“…That self‐identity predicted intentions after TPB components were accounted for is consistent with much previous research (e.g., Booth et al., ; Nigbur et al., ; Ries et al., ). However, that this effect was found even though we included a measure of perceived importance serves to extend previous research.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…That self‐identity predicted intentions after TPB components were accounted for is consistent with much previous research (e.g., Booth et al., ; Nigbur et al., ; Ries et al., ). However, that this effect was found even though we included a measure of perceived importance serves to extend previous research.…”
Section: Discussionsupporting
confidence: 89%
“…Self-identity predicts intentions after standard TPB components have been accounted for in a range of behavioural contexts, including physical activity (Jackson, Smith, & Conner, 2003;Ries, Hein, Pihu, & Armenta, 2012), alcohol consumption (Conner, Warren, Close, & Sparks, 1999), sexual health (Booth, Norman, Harris, & Goyder, 2014), environmental activism (Fielding, McDonald, & Louis, 2008), and recycling (Mannetti, Pierro, & Livi, 2004;Nigbur, Lyons, & Uzzell, 2010;Terry et al, 1999). Further, a meta-analysis of 40 studies found that self-identity enhanced the prediction of intentions beyond TPB components, accounting for 6% of additional variance in intentions (Rise et al, 2010).…”
Section: Self-identitymentioning
confidence: 99%
“…According to Ajzen (1991), the TPB is open to further expansion as long as a strong theoretical justification for the inclusion of additional predictors is provided. Consequently, several recent studies have added variables in the TPB, such as self-identity (Ries, Hein, Pihu, & Armenta, 2012), past behaviour (Norman, Conner, & Bell, 2000), group norms, family social support, friends, social support and social provisions (Hamilton & White, 2008), past behaviour and anticipated negative emotions (Wang, 2011) and self-efficacy and past behaviour (Hagger, Chatzisarantis, Biddle & Orbell., 2001), to predict adolescent physical activity intention and behaviour. These variables have accounted for some of the additional variance in behavioural intentions or behaviours over the TPB constructs.…”
Section: Theory Of Planned Behaviourmentioning
confidence: 98%
“…Recently, two variablesself-identity and descriptive normhave been discussed for inclusion as additional predictors of exercise intention and behavior within the TPB. 4,5 Subjective norm has been identified as the individual's perception about what significant others think ought to be done. 6 Recently, Ajzen and Fishbein stated that the subjective norm construct should also include the individual's perception about what significant others do (descriptive norm).…”
Section: Introductionmentioning
confidence: 99%
“…13 A meta-analysis found that self-identity could exert a direct influence on behavior itself in the exercise domain. 5 Despite the research supporting the influence of self-identity on behavioral intention, there is no research exploring the role of self-identity within the TPB in relation to exercise in Chinese patients with type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%